Communication Model for Developing Tourism Potentials in Solop Beach, Riau - HARTO, Syafri (Journal of Environmental Management and Tourism, 2019)
The objectives of the study are to develop communication model for developing tourist potentials in Solop Beach, Indragiri Hilir, Riau, and to analyze both public and government participation on tourist management in Solop Beach, Indragiri Hilir, Riau. The setting of the study was Solop Beach located in Indragiri Hilir, Riau. It used descriptive qualitative method in which interview and field observations were the data collection methods. The populations were people living around Solop Beach, Indragiri Hilir, Riau. The total population was 800 families. The number of sample was 100 people. The sampling technique was non-probality sampling. Primary data referred to information obtained from the interviews and field-observation in Solop Beach while secondary data, additional information that complemented the primary data, referred to the theories from relevant literatures as well as findings of previous studies and documents obtained from the Department of Tourism, National Statistics Bureau and Bappeda of Indragiri Hilir. Transactional model of communication and knowledge-sharing are two channels of communication Department of Tourism of Indragiri Hilir used to develop tourist potentials in Solop Beach, Indragiri Hilir, Riau. The most frequent line of communication in the models are interpersonal, group and public communication. Roles of the regional government in Solop Beach are providing infrastructure and public facilities, promotion and involving the locals in program of which purpose is to develop tourism sector in Beach. The beach needs better public facilities because of growing number of visitors. The locals take active participation in government programs to develop tourism sector in this beach. They join “sadar wisata” community group and attend training on tourism the regional government conducts.